Mental illness stigma, secrecy and suicidal ideation. (26th November 2015) - Oexle, N.; Ajdacic-Gross, V.; Kilian, R.; Müller, M.; Rodgers, S.; Xu, Z.; Rössler, W.; Rüsch, N.
Abstract : Aims: Whether the public stigma associated with mental illness negatively affects an individual, largely depends on whether the person has been labelled 'mentally ill'. For labelled individuals concealing mental illness is a common strategy to cope with mental illness stigma, despite secrecy's potential negative consequences. In addition, initial evidence points to a link between stigma and suicidality, but quantitative data from community samples are lacking. Methods: Based on previous literature about mental illness stigma and suicidality, as well as about the potential influence of labelling processes and secrecy, a theory-driven model linking perceived mental illness stigma and suicidal ideation by a mediation of secrecy and hopelessness was established. This model was tested separately among labelled and unlabelled persons using data derived from a Swiss cross-sectional population-based study. A large community sample of people with elevated psychiatric symptoms was examined by interviews and self-report, collecting information on perceived stigma, secrecy, hopelessness and suicidal ideation. Participants who had ever used mental health services were considered as labelled 'mentally ill'. A descriptive analysis, stratified logistic regression models and a path analysis testing a three-path mediation effect were conducted. Results: While no significant differences between labelled and unlabelled participants were observed regarding perceived stigma and secrecy, labelled individuals reported significantly higher frequencies of suicidal ideation and feelings of hopelessness. More perceived stigma was associated with suicidal ideation among labelled, but not among unlabelled individuals. In the path analysis, this link was mediated by increased secrecy and hopelessness. Conclusions: Results from this study indicate that among persons labelled 'mentally ill', mental illness stigma is a contributor to suicidal ideation. One explanation for this association is the relation perceived stigma has with secrecy, which introduces negative emotional consequences. If our findings are replicated, they would suggest that programmes empowering people in treatment for mental illness to cope with anticipated and experienced discrimination as well as interventions to reduce public stigma within society could improve suicide prevention.